Do Environmental, Social, and Governance Performance Impact Firm Performance? Evidence from Indian Firms - Ajay Lunawat; Dipti Lunawat (Indonesian Journal of Sustainability Accounting and Management, 2022)
This paper investigates the impact of individual environmental (E), social (S), and governance (G) and the overall ESG performance on the firms’ performance in Indian context. Three dimensions of a firm’s performance, i.e., operational, financial, and market performance, are measured through return on assets, return on equity, and firm value (Tobin’s Q), respectively. The study spans the period from 2012 to 2019, with NSE 500 firms as the first sample set and NSE 100 ESG enhanced index firms as the second sample set. Panel data analysis was performed with efficiency tests for the random and fixed-effects models. The study deduced that the ESG index listed firms have better operational and financial performance than the non-listed ESG firms. With the second sample set, the impact of ESG and its subcomponents’ performance on firms’ performance was examined. Overall, ESG had a positive and significant association with operational and market performance. All the subcomponents positively impact operational performance and negatively impact market performance. The impact of ESG and its subcomponents on financial performance could not be established except for the governance score. The study findings will be beneficial for investors, regulators, and corporate sustainability decision-makers in their different capacities and roles across global markets.